Early empiric antibiotic use in preterm infants is associated with lower bacterial diversity and higher relative abundance of Enterobacter - Greenwood, Corryn (2014)
OBJECTIVES: To determine the impact of empiric ampicillin and gentamicin use in the first week of life on microbial colonization and diversity in preterm infants. STUDY DESIGN: 16s rDNA community profiling was used to compare the microbiota of 74 infants born ≤32 weeks gestational age by degree of antibiotic use in the first week of life. The degree of antibiotic use was classified as 0 days, 1-4 days and 5-7 days of antibiotic administration. . All of the antibiotic use was empiric, defined as treatment based solely on clinical suspicion of infection without a positive culture result. RESULTS: Infants who received 5-7 days of empiric antimicrobial agents in the first week had increased relative abundance of Enterobacter (p=0.016) and lower bacterial diversity in the second and third weeks of life. Infants receiving early antibiotics also experienced more cases of NEC, sepsis or death than those not exposed to antibiotics. CONCLUSIONS: Early empiric antibiotics have sustained effects on the intestinal microbiota of preterm infants. Intestinal dysbiosis in this population has been found to be associated with elevated risk of necrotizing enterocolitis, sepsis, or death.